Clinical manifestations and genetic analysis of a newborn with Arboleda−Tham syndrome - Zeng, Feng; Yang, Yue; Xu, Zhaohui; Wang, Ziwen; Ke, Huan; Zhang, Jianhong; Dong, Tongtong; Yang, Wenming; Wang, Jiuxiang (Frontiers in Genetics, 2022)
Arboleda−Tham syndrome (ARTHS) is a rare disorder first characterized in 2015 and is caused by mutations in lysine (K) acetyltransferase 6A (KAT6A, a.k.a. MOZ, MYST3). Its clinical symptoms have rarely been reported in newborns from birth up to the first few months after birth. In this study, a newborn was diagnosed with ARTHS based on the clinical symptoms and a mutation c.3937G>A (p.Asp1313Asn) in KAT6A. The clinical manifestations, diagnosis, and treatment of the newborn with ARTHS were recorded during follow-up observations. The main symptoms of the proband at birth were asphyxia, involuntary breathing, low muscle tone, early feeding, movement difficulties, weak crying, weakened muscle tone of the limbs, and embrace reflex, and facial features were not obvious at birth. There was obvious developmental delay, as well as hypotonic and oro-intestinal problems in the first few months after birth. Mouse growth factor was used to nourish the brain nerves, and touching, kneading the back, passive movements of the limbs, and audio−visual stimulation were used for rehabilitation. We hope that this study expands the phenotypic spectrum of this syndrome to newborns and the library of KAT6A mutations that lead to ARTHS. Consequently, the data can be used as a basis for genetic counseling and in clinical and prenatal diagnosis for ARTHS prevention.